Volume 5: Turbo Expo 2005 2005
DOI: 10.1115/gt2005-68729
|View full text |Cite
|
Sign up to set email alerts
|

Engine Performance Improvement by Controlling the Low Pressure Compressor Working Line

Abstract: The new algorithm provides closed-loop control of the LP Compressor working line in such a way as to maintain compressor stability and to provide increased power from the engine at the same firing temperature. This method is intended for the Trent 60, an aero-derivative engine designated for power generation and mechanical drive applications. The power benefit is achieved by operating at higher LPC pressure ratio and thereby increasing the inlet air flow and overall pressure ratio of the engine. Since the algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The amount of power improvement for an industrial gas turbine at ambient temperature from 25 to 45 C is reported to be about 3% in some reference. 1 However, in that reference, only IGV angle was adjusted and the compressor operating point become close to the surge line (lower surge margin). It should be noted that the engine power output in load control mode is set to be at the optimum value of power output in TIN control mode (Table 7) for comparison of the life cycle results.…”
Section: Optimization Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of power improvement for an industrial gas turbine at ambient temperature from 25 to 45 C is reported to be about 3% in some reference. 1 However, in that reference, only IGV angle was adjusted and the compressor operating point become close to the surge line (lower surge margin). It should be noted that the engine power output in load control mode is set to be at the optimum value of power output in TIN control mode (Table 7) for comparison of the life cycle results.…”
Section: Optimization Resultsmentioning
confidence: 99%
“…Martis et al 1 proposed a new closed-loop control algorithm for IGV and bleed valve opening to increase the pressure ratio while compressor stability is also maintained. This provides power output and efficiency increase without any augmentation in turbine inlet temperature (TIT).…”
Section: Introductionmentioning
confidence: 99%